Gold catalysis: biarylphosphine ligands as key for the synthesis of dihydroisocoumarins - Hashmi, A. Stephen K.; Bechem, Benjamin; Loos, Annette; Hamzić, Melissa; Rominger, Frank; Rabaa, Hassan (Australian journal of chemistry, 2014)
A gold-catalyzed phenol synthesis was successfully used in the synthesis of dihydroisocoumarins for the first time. A large number of gold(i) complexes were prepared and tested; only complexes based on the biarylphosphine motif were successful.